HUBUNGAN MOTIVASI ORANGTUA UNTUK MENCAPAI KESEMBUHAN ANAK DENGAN TINGKAT PENGETAHUAN TENTANG PENANGANAN ANAK PENYANDANG AUTISME DAN SPEKTRUMNYA - Asmika, Asmika; Andarini, Sri; Rahayu, Ririn Puji (Fakultas Kedokteran Universitas Brawijaya, 2006)
ABSTRACT The incidence of children with autisme spectrum disorder has rapidly increased, starting fom 1:1500 in 1987 to1:100 in year 2001. The parent’s motivation for actively being involved in treatment programs, such as consultation with the expert and improvement of their knowledge will increase the treatment success up to 80%. Therefore it is of paramount importance to identify the parent’s motivation and knowledge about Autisme treatment as a baseline for improving parent’s active involvement. A cross sectional research design was carried out using twenty parents (mother/father or both) as responden is in Autisme treatment center: A-Plus’ Dharma Wanita PUNM Malang District from15 April - 31 May 2003. The parents motivation and knowledge level was measured using close ended questionnaire. In general, autisme is mostly identified in male child (55%), first child (45%)and diagnosed by children specialist or psychiatrist (75%) at the age of 0-2 year (75%). Most of the parents (85%) have a high motivation in gaining children healing but 60% parents have low knowledge level about Autisme treatment with mass media as the main information source (85%). There is no significant relationship (p > 0,05)between parent’s motivation and knowledge level. Key Words: motivasi, pengetahuan orang tua, Autisme dan spektrumnya